1998
DOI: 10.1172/jci1478
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial fluid clearance is mediated by endogenous catecholamines at birth in guinea pigs.

Abstract: Transition from placental to pulmonary oxygenation at birth depends on a rapid removal of fetal lung fluid from the developing alveoli. Alveolar fluid clearance was examined in ventilated, anesthetized developing guinea pigs of the ages newborn, 2-d-old, 5-d-old, 30-d-old, and 60-d-old (adult). An isosmolar 5% albumin solution was instilled into the lungs of the guinea pigs; the guinea pigs were then studied for 1 h. Alveolar fluid clearance was measured from the increase in alveolar protein concentration as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
139
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(147 citation statements)
references
References 49 publications
8
139
0
Order By: Relevance
“…Studies in guinea pig showed that both ␣-ENaC mRNA expression and the sensitivity of lung liquid clearance to amiloride and to ␤-adrenoceptor blockade were highest shortly after birth and declined in parallel with endogenous plasma epinephrine concentration (30), providing further support for the key role of ␤-adrenoceptor activation of Na ϩ channels at birth. However, because ␣-ENaC mRNA expression rapidly increases after caesarean section in late gestation and at term in guinea pig lungs (4), it would appear that the upregulation of this particular Na ϩ channel subunit is not related to labor.…”
Section: Molecular Expression Of Key Transport Proteins During Develomentioning
confidence: 91%
“…Studies in guinea pig showed that both ␣-ENaC mRNA expression and the sensitivity of lung liquid clearance to amiloride and to ␤-adrenoceptor blockade were highest shortly after birth and declined in parallel with endogenous plasma epinephrine concentration (30), providing further support for the key role of ␤-adrenoceptor activation of Na ϩ channels at birth. However, because ␣-ENaC mRNA expression rapidly increases after caesarean section in late gestation and at term in guinea pig lungs (4), it would appear that the upregulation of this particular Na ϩ channel subunit is not related to labor.…”
Section: Molecular Expression Of Key Transport Proteins During Develomentioning
confidence: 91%
“…IL-1␣ also improved postnatal lung function with increased surfactant pool size without eliciting systemic inflammatory responses in lambs (14, 47). We recently reported that IL-1␤ pretreatment of timed-pregnant guinea pigs induced fluid absorption in fetal lungs, sodium transporter protein, and ␤-adrenoceptor expression via hypothalamus-pituitary-adrenal gland axis stimulation (48).Lung fluid absorption occurs secondarily to transepithelial Na ϩ absorption (3,5,8,17,22,31,35,37,45,48,49) and is driven by basolateral Na-K-ATPases (16, 23) and apical epithelial sodium channels (19,22,30,31). Fluid absorption occurs in near-term lungs (6,17,35,37,45) and is induced/ stimulated by cortisol and triiodothyronine (2, 20, 48) and labor-released epinephrine (17,35,45).…”
mentioning
confidence: 99%
“…Fluid absorption occurs in near-term lungs (6,17,35,37,45) and is induced/ stimulated by cortisol and triiodothyronine (2,20,48) and labor-released epinephrine (17,35,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the role of PDE4 in hormonal pathways (Mehats et al, 2002), one may speculate that at birth, hormonal regulations of postnatal lung physiology begin to be tightly regulated by selective PDE4s. Notably, clearance of fetal lung fluid is initiated secondary to beta-adrenergic-stimulated Na þ transport near term or at birth (Finley et al, 1998). Because PDE4D5 and PDE4D8 have been recently implicated in regulation of beta2-and beta1-adrenergic Fig.…”
Section: Discussionmentioning
confidence: 99%